Alternatif Penyelesaian Sengketa Waralaba (Franchise) Melalui Arbitrase di Indonesia - Prayudy Widyanto; Yasarman Yasarman (LPPM Iblam School of Law, 2026)
This study analyzes the legal framework and effectiveness of franchise dispute resolution through arbitration in Indonesia. It addresses two main questions: (1) how the law regulates dispute resolution in franchise agreements, and (2) the advantages and disadvantages of arbitration compared to general courts. The research uses a Systematic Literature Review (SLR) guided by the PRISMA protocol, with data collected from the Google Scholar database (2000–2024) using the Publish or Perish software. Out of 100 identified articles, 38 met the inclusion criteria. The findings show that 79% of the articles use normative juridical methods, while 21% combine normative and empirical approaches. The legal framework for franchise agreements includes the Indonesian Civil Code, Government Regulation No. 42/2007, and Minister of Trade Regulation No. 71/2019. Arbitration is viewed as efficient, confidential, final, and flexible, but it faces challenges like high costs and the need for court involvement in enforcing awards. The study concludes that while the legal framework for franchise dispute resolution is comprehensive, its effectiveness depends on consistent implementation.